Native chicken farming: A tool for wealth creation and food security - ADOLIGBE, CAMUS; Fernandes, Arthur; Osei-Amponsah, Richard (My University, 2020)
Poultry is the second largest livestock in Benin (contributing to 22% of the total meat produced), and chickens are the most reared poultry in the country. The objective of this study was to assess the current trends of local chicken breeding and factors that influence their production performance, and thereby to deliver information for production improvement and sustainable use of indigenous chicken breeds. An electronic tool was used to collect information from 269 respondents selected through a chain referral sampling method. The results showed that there were three production systems; however, the most common production system used was free-range extensive system (70%). Regarding flock ownership, men owned the birds in the majority of the cases (63%) and had overall higher population of chickens than women. The most predominant constraints for chicken production, in descending order of importance, included theft, access to bank loan, lack of training, limited investment, disease spread and mortality. From our results, gender, financial resources, main activity of the flock owner, weaning practice, and the production area had a significant effect on flock size. To enhance the indigenous chicken production, changes in traditional management practices combined with breeding program focusing on within breed selection (closed nuclear system) is a better approach.
Keywords: Biodiversity; cluster analysis; food security; farmer livelihood; local chickens.